Legal Analysis of the Modus Operandi of Drug Trafficking Using the Outboard System in Cirebon - Noviandy, Mochamad Ryan; Jatmika, Bambang Dwi; Rahman, Alip; Daulay, Annisa Angraini (PT FORMOSA CENDEKIA GLOBAL, 2025)
Drug trafficking in Cirebon City showed a significant increase between 2019 and 2021, with the modus operandi of the outboard system growing rapidly. In this mode, the perpetrator hides the drugs in a specific location for the buyer to pick up without direct interaction. This study aims to evaluate the judge's decision against the perpetrators of narcotics crimes who apply the modus operandi of the sticky system and examine the law's application in the case. The method used is normative juridical, with an emphasis on reviewing the provisions of laws and regulations, especially Law Number 35 of 2009 concerning Narcotics. The data analyzed is secondary data obtained from various legal references, such as books, court rulings, and other relevant documents. Data collection is carried out through literature studies and legal document reviews. The study results show that the outboard mode in Cirebon reduces direct contact between perpetrators and buyers by involving organized crime that utilizes technology. Law enforcement against this mode faces various challenges, including the difference in punishment in the Cirebon District Court decision Number 90/Pid.Sus/2021/PN Cbn sentenced him to four years in prison and a fine. Law enforcement against the modus operandi of the drug trafficking outboard system in Cirebon faces challenges in proving and disclosing the perpetrator network, even though intelligence strategies, undercover operations, and inter-agency collaboration have been implemented.